Sosialisasi Vaksinasi Human Papilloma Virus di SMK Negeri 1 Pangkalan Kerinci - Rahmat Azhari Kemal; Frilianty Putri; Indah Nur Ramadhan; Fadhlatul Jannah; Bimo Diokta Alparisi; Nadya Adha Nasution; Diva Afdholia; Darma Lutfi Ananda; Aufa Rahmatullah; Regita Mayang Rahmi; Risma Diana; Pedro De Gibran (Tamkin Jurnal Pemberdayaan Tazkia, 2026)
Cervical cancer is among the cancers with a high mortality rate. Therefore, it is crucial to understand and prevent this cancer. One of the preventive measures is through vaccination against the causal pathogen, Human papillomavirus (HPV). One of the target groups in cervical cancer prevention is teenagers in high school. To enhance the understanding of cervical cancer and HPV vaccine, an educational campaign was provided to SMK Negeri 1 Pangkalan Kerinci students. The students were given educational videos through Instagram social media as well as a face-to-face lecture. The result showed an increase in the students’ knowledge on cervical cancer and HPV vaccine. This activity showed that Instagram social media can be utilised as a health education medium to teenagers.